Refugee children's earnings in adulthood - Yoko Yoshida; Jonathan Amoyaw; Rachel McLay (IZA World of Labor, 2022)
The number of refugees has increased worldwide, and about half of them are children and youth. These refugee children arrive in resettlement countries with a unique set of challenges caused by, for instance, extreme stress and trauma that call for specific policies to address their needs. Yet, the long-term effect of refugee status on newcomer children's economic trajectories varies by country of origin, signaling the need for effective resettlement support and initiatives to tackle broader systemic barriers for newcomer children, beyond refugees. Such findings challenge the commonly held notion of refugees as a distinctive, relatively homogeneous group with similar trajectories.
Keywords: J6; J15; 330; refugees; immigrants; children; earning trajectories; race; ethnicity